STUDI PERBANDINGAN PEMBELAJARAN KOOPERATIF MENGGUNAKAN MEDIA KARTU PINTAR DAN KARTU KEMUDI PINTAR - Yova Andela Sari; Amrul Bahar; Salastri Rohiat (University of Bengkulu, 2017)
The problem of learning process that often occur in classroom that the use of conventional learning method. This makes the lack of student activeness in the process and makes the students' low learning outcomes . So that researchers interested in finding variations of teaching by combining the learning model with instructional media. The use of this media is taken into consideration from its practicality, strength, and effectiveness. The type of research used is quasi experimental research with population class XI IPA in SMAN 8 Bengkulu and sample is class XI IPA 2 and class XI IPA 3. The sample in this research is by applying smart card media for experiment class 1 (XI IPA 3) With the experimental class 2 (XI IPA 2) using smart steering card media on salt hydrolysis topics. Data analysis used are mean value, homogeneity test, normality test, t test and questionnaire analysis. The average value of posttest experiment class I is 76.875, while for experimental class II is 80,85. Then t test with significant level (? = 0,01), then got tcount value equal to 5,41 and 2,39 for table . The results showed that there were significant differences in learning outcomes between the smart card media class and the smart media grade of the steering wheel on the salt hydrolysis topics.